PENERAPAN MANAJEMEN KELAS DALAM PERKEMBANGAN SOSIAL DAN EMOSIONAL ANAK USIA DINI KELOMPOK A DI TK KEMALA BHAYANGKARI 47 - Yulia Afandi; Hani Ida Kusuma (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Yulia Afandi, et al. This research starts from the main problem that is about: "How the implementation of classroom management in improving emotional social development of early childhood in Group A TK Kemala Bhayangkari 47". The method used in this research is qualitative with descriptive method. This study intends to obtain empirical data about how the implementation of classroom management in improving social development of early childhood in Group A TK Kemala Bhayangkari 47. The authors define the method used in this research is descriptive method with the consideration that this method is a way researchers by describing events present or present. The results of the study were: 1) Implementation of Classroom Management in Emotional Social Development of Early Childhood in Kemala Bhayangkari Kindergarten 47 In the early childhood management class should be oriented to the characteristics of early childhood development. Understanding teachers about the characteristics of children will be useful in an effort to create a learning environment that supports child development. In general it can be said that the main guidance given to children include: In the organization of children in classes conducted in Kemala Bhayangkari Kindergarten 47 can be done by: Grouping children, Paired grouping (grouping in pairs), Multi grouping. 2) Implementation of Classroom Management in Developing Early Childhood Emotional Social in Kemala Bhayangkari Kindergarten 47 develops classroom management activities based on the understanding of learning concepts and development-oriented and the characteristics of early childhood. 3) Supporting Factors and Inhibitors of Classroom Management Implementation in Developing Social and Emotional Early Childhood in Kemala Bhayangkari Kindergarten 47, among others: the supporting factors of class management manifestation are: a) Curriculum factors, b) Building factors and classroom facilities. The Inhibiting Factor Application of classroom management in developing social and emotional early childhood in kindergarten Kemala Bhayangkari 47, including: Physical environment factor, physical environment / learning place.